Amyloid beta-protein activates tachykinin receptors and inositol trisphosphate accumulation by synergy with glutamate. - Kimura, H (1993)
The biological function of the soluble form of the amyloid beta-protein (ABP) was examined by assaying its interaction with neuronal receptors expressed in Xenopus oocytes. ABP weakly activated tachykinin receptors, but in the presence of N-methyl-D-aspartate and alpha-amino-3-hydroxy-5-methylisoxazole-4- propionate-type glutamate receptors ABP-induced responses were greatly enhanced. Glutamate and ABP together also induced accumulation of inositol trisphosphate and increases in intracellular Ca2+. These observations suggest that in the presence of glutamate, ABP can activate tachykinin receptors and phosphatidylinositol turnover. ABP may therefore act as a neuromodulatory peptide.